HIV-1 molecular diversity and drug resistance mutations amongst immuno-competent, therapy naïve infants/children and adults in Yaounde, Cameroon - Gichana, Josiah Otwoma (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScMedSc)--Stellenbosch University, 2017.